Union Mergers and International Unionism in Canada - Chaison, Gary (Relations industrielles / Industrial Relations, 1979)
The purpose of this paper is to highlight the difficulties en-countered in using mergers to reduce the number of unions in a country with both national and international organizations. it is seen that the presence of internationals limits the scope of potential mergers and that merger attempts can strain the relations between the Canadian sections of international unions and their parent unions.